Skin biopsy as an alternative to muscle biopsy for the diagnosis of Ullrich congenital muscular dystrophy - Sharma, Mehar Chand (Journal of Pediatric Neurology, 2012)
The aim of this study was to assess the diagnostic utility of skin biopsy in the diagnosis of Ullrich congenital muscular dystrophy. Paired skin and muscle biopsies were, studied in the three cases of Ullrich disease. Immunostaining for collagen VI was performed on both test and control biopsies. Staining pattern in skin biopsies was compared with the muscle biopsies. Immunoblot was performed to validate the results. Immunostaining for collagen VI was absent in dermis in skin biopsies of all the three patients of Ullrich disease and corroborated with findings of muscle biopsies. Immunoblot revealed absence of collagen VI band in all the three cases. Our study suggests that skin biopsy can be very useful for the diagnosis of Ullrich disease. Skin biopsy being less traumatic and less invasive is easy to perform in children, obviates the need for sedation, and is cosmetically superior to muscle biopsy.
Keywords: Collagen VI; muscle biopsy; skin biopsy; Ullrich disease; muscular dystrophy